Managerial Tacit Knowledge, Individual Performance, and the Moderating Role of Employee Personality - Abdul Manaf, Halimah; Armstrong, Steven J.; Lawton, Alan; Harvey, William S. (Routledge, 2017)
This study investigates the relationship between knowledge-sharing mechanisms, managerial tacit knowledge, and individual performance in the Malaysian public sector. Moderation effects of employee personality on these variables were also examined.Findings from 308 Malaysian public sector managers suggest that individual performance is influenced by levels of accumulated managerial tacit knowledge (LAMTK), which were moderated by employee personality traits.The findings also show that individual performance has an impact on the effectiveness of knowledge-sharing mechanisms.